2023
DOI: 10.1007/s42843-023-00078-9
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Inequity, Burnout, and Lower Engagement of Women in Medicine

Abstract: Gender parity has been reached in graduation rates from medical school, yet women in medicine continue to face obstacles in promotion, compensation and opportunities, leading to leadership inequity, higher burnout and lower engagement. These complex issues with gender are just one aspect of the wide challenges related to diversity, equity and inclusion among medical professionals. While there are no “one size fits all” approaches, psychologists are well positioned to lead efforts related to promoting leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although the numbers of women practicing medicine are increasing, system-level interventions to support women experiencing role strain are lacking. For a recent, thoughtful discussion of burnout, engagement, and common gender-specific stressors experienced by women in medicine, please see Sullivan et al ( 2023 ).…”
Section: Burnout In Underrepresented Marginalized and Vulnerable Groupsmentioning
confidence: 99%
“…Although the numbers of women practicing medicine are increasing, system-level interventions to support women experiencing role strain are lacking. For a recent, thoughtful discussion of burnout, engagement, and common gender-specific stressors experienced by women in medicine, please see Sullivan et al ( 2023 ).…”
Section: Burnout In Underrepresented Marginalized and Vulnerable Groupsmentioning
confidence: 99%
“…Fear of repercussion may be one factor preventing physicians from seeking individual treatment for burnout. 38 Importantly, they emphasize the need for professional confidentiality when offering treatment to patients within organizational settings. Those authors also reported that a focus on organizational engagement may be an important factor in addressing burnout in female physicians, as they tend to report lower levels of organizational engagement.…”
Section: Management Strategiesmentioning
confidence: 99%
“…However, even in many medical specialties where gender parity has been achieved, women still lag behind in leadership positions, academic advancement, and career satisfaction. 2 A 2021 review of 39 studies on female neurosurgeons globally found that the most cited factors explaining the gender gap in neurosurgery were lifestyle factors such as family life and achieving personal goals. 1 Outside of these factors, female neurosurgeons also face considerable professional challenges including being less likely to occupy leadership roles, attain full professorships, and serve as division chiefs, chairs, or program directors.…”
mentioning
confidence: 99%